The make-up of a regression coefficient: gender gaps in the European labor market - Pittau, Maria Grazia; Yitzhaki, Shlomo; Zelli, Roberto (Roma, 2013)
"We provide a comprehensive picture of the relationship between labor market outcomes and age by gender in all the 28 European countries covered by the European Statistics on Income and Living Conditions (EU-SILC). The analysis is based on a somewhat unconventional approach that refers to concentration curves in the context of Gini regression framework. It allows to identify ranges in the explanatory variables where local slopes change sign and/or size, i.e. the components that \make up" a regression coecient. The European countries are clustered into five groups according to their employment, hours of work and earnings age-profiles by gender, as identified by the concentration curves. The most relevant differences in age proles concern working-hours-patterns: some countries are characterized by an almost specular behavior in men and women; other countries instead show similar patterns. Generally, earnings increase with age for both men and women. However, local regression coefficients are not monotonic over the entire age range and can even be locally negative in some countries."